Pedagogy, curriculum and special education: a case study in China - Cai, Lily; Dearden, Jackie; Jin, Xiaojing (Wiley, 2019)
This study uses a conceptual framework devised by Norwich and Lewis in the UK in 2007 to examine the education of children with special educational needs and disabilities (SEND) in China. Norwich and Lewis, whose expressed intention was to offer ‘a starting point for setting out a coherent and common framework of teaching that is inclusive’ (2005, p. 219), called for research to further develop their work. In that spirit, this article reports an exploratory case study of pedagogy in a Chinese special school analysed using Norwich and Lewis’s conceptual framework. The example of practice in China provides a platform for reflection and challenge to existing theories and practices in other contexts, but also a chance to reflect upon the utility of the framework itself. In this regard, the authors suggest that Norwich and Lewis’s conceptual framework provides a helpful lens for analysing inclusive pedagogic practice but that teachers’ self-knowledge about their own expectations of students needs to feature more centrally.